Integrated transcriptomic and metabolomic analysis reveals the molecular profiles of dynamic variation in Lilium brownii var. viridulum suffering from bulb rot - Chang, Nana; Zheng, Lingling; Xu, Yang; Wang, Chu; Li, Hui; Wang, Ye (Frontiers in Genetics, 2024)
Lilium brownii var. viridulum, known as Longya lily, is a well-known medicinal and edible plant in China. Bulb rot is a common disease in Longya lily cultivation that severely affects the yield and quality of lilies. According field investigations, we found that different Longya lily plants in the same field had different degrees of resistance to root rot. To find the reasons leading to the difference, we performed metabolomic and transcriptomic analyses of Longya lily with different degrees of disease. The transcriptomic analyses showed that the number of differentially expressed genes increased in early and mid-stage infections (LYBH2 and LYBH3), while decreased in late-stage infection (LYBH4). A total of 2309 DEGs showed the same expression trend in diseased bulb compared healthy bulb (LYBH1). The transcription factors (TFs) analysis of DEGs showed that several common TFs, like WRKY, bHLH, AP2/ERF-ERF and MYB, were significantly activated in bulbs after decay. The metabolomic analyses showed that there were 794 differentially accumulated metabolites, and metabolites with significant changes in relative content largely were phenolic acids, followed by flavonoids and amino acids and derivatives. The combined analysis of transcriptome and metabolome indicated that phenylpropanoid biosynthesis pathway was crucial in Longya lily resistance to bulb rot. Therefore, we speculated that the different degree of resistance to bulb rot in Longya lily may be related to the transcript levels of gene and contents of metabolites in the phenylpropanoid biosynthesis pathway. Overall, these results elucidate the molecular responses of Longya lily to bulb rot and lay a theoretical foundation for breeding resistant varieties.